Sentinel lymph node mapping with indocyanine green in cervical cancer patients undergoing open radical hysterectomy: a single-institution series - Bizzarri, Nicolò (J Cancer Res Clin Oncol, 2020)
PURPOSE: To assess the rate of bilateral sentinel lymph node (SLN) detection with indocyanine green (ICG), to evaluate the sensitivity and the negative predictive value of cervical cancer patients undergoing open radical hysterectomy; to compare open versus minimally invasive SLN biopsy performance and to assess factors related to no/unilateral SLN mapping. METHODS: We retrospectively reviewed consecutive patients with FIGO 2018 stage IA1 with lymph-vascular space involvement to IIB and IIIC1p cervical carcinoma who underwent SLN mapping with ICG followed by systematic pelvic lymphadenectomy between 05/2017 and 06/2020. Patients were divided according to surgical approach for statistical analysis. RESULTS: Eighty-five patients met inclusion criteria. Twenty-seven (31.8%) underwent open and 58 (68.2%) underwent minimally invasive SLN mapping. No difference in any SLN mapping (laparotomy 92.6% and minimally invasive 91.4%) or in SLN bilateral detection (laparotomy 72.0% and minimally invasive 84.9%) (p = 0.850 and p = 0.222, respectively), in median number of SLNs mapped and retrieved (2 in both groups, p = 0.165) and in site of SLN mapping per hemi-pelvis (right side, p = 0273 and left side, p = 0.618) was evident between open and minimally invasive approach. Per-patient sensitivity of SLN biopsy in laparotomy was 83.3% (95% CI 35.9–99.6%) and the negative predictive value was 95.0% (95% CI 76.0–99.1%). No difference in per-patient sensitivity was noted between two approaches (p = 0.300). None of the analyzed variables was associated with no/unilateral SLN mapping. CONCLUSION: The use of ICG to detect SLN in cervical cancer treated with open surgery allows a bilateral detection, sensitivity and negative predictive value comparable to minimally invasive surgery with potential advantages of ICG compared to other tracers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00432-020-03393-6) contains supplementary material, which is available to authorized users.